Jalan panjang pemberantasan korupsi - Jaweng, Robert Endi.; Partnership for Governance Reform in Indonesia (Kebayoran Baru, Jakarta : Kemitraan bagi Pembaruan Tata Pemerintahan di Indonesia, 2011)
Strategies to combat corrupt practices in Indonesia.
Includes bibliographical references (p. 171-173).
Keywords: Corruption -- Indonesia; Corruption -- Prevention; Political corruption -- Indonesia